2017 Asia-Pacific Signal and Information Processing Association Annual Summit and Conference (APSIPA ASC) 2017
DOI: 10.1109/apsipa.2017.8282270
|View full text |Cite
|
Sign up to set email alerts
|

Identifying computer-generated text using statistical analysis

Abstract: Computer-based automatically generated text are used in various applications (e.g. text summarization, machine translation) and such the machine-generated text significantly helps our social life. However, machine-generated text may produce confusing information sometimes due to errors or inappropriate use of wordings caused by language processing, which could be a critical issue in president elections or in product advertisements. Previous methods for detecting such machinegenerated text typically estimates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 9 publications
(18 reference statements)
0
18
1
Order By: Relevance
“…The limitation of this model is that meaningful features are only given from few nearby words, common in three. Other work [5,9] analyzes the histogram of word distribution from a massive amount of words, particularly suitable for document level. A recent method [10], the closest one to this paper, estimates text coherence by mutually matching words across pairwise sentences using word similarity.…”
Section: Machinetranslated Paragraph Pmmentioning
confidence: 99%
See 4 more Smart Citations
“…The limitation of this model is that meaningful features are only given from few nearby words, common in three. Other work [5,9] analyzes the histogram of word distribution from a massive amount of words, particularly suitable for document level. A recent method [10], the closest one to this paper, estimates text coherence by mutually matching words across pairwise sentences using word similarity.…”
Section: Machinetranslated Paragraph Pmmentioning
confidence: 99%
“…This metric is perfectly used for classifying artificial and real papers with accuracy up to 100%, but Nguyen-Son et at. [9] indicated that the inter-textual metric is just suitable for paper detection and they developed another method for translation detection also based on word distribution. This method pointed out that a word distribution of human text is closer with a Zipfian distribution than that of machine one.…”
Section: Word Distributionmentioning
confidence: 99%
See 3 more Smart Citations